A comparatively study of menaquinone-7 isolated from Cheonggukjang with vitamin K1 and menaquinone-4 on osteoblastic cells differentiation and mineralization. (September 2019) - Wu, Wei-Jie; Gao, Haiyan; Jin, Jong-Sik; Ahn, Byung-Yong
Abstract: The effect of menaquinone-7 isolated from cheonggukjang was comparatively investigated with vitamin K1 and menaquinone-4 on cell differentiation and mineralization of the osteoblastic cell line MC3T3-E1. Results indicated that all vitamin K species significantly increased MC3T3-E1 cell proliferation, cellular alkaline phosphatase activity, osteocalcin synthesis, and calcium deposition in a dose-dependent manner. Menaquinone-4 and menaquinone-7 had more potent effects on calcium deposition than vitamin K1, and their effects were only partly reduced by warfarin (γ-carboxylation inhibitor) treatment, while warfarin abolished the induction activity of vitamin K1 on calcification. This suggests that vitamin K1 and K2 (menaquinone-4 & menaquinone-7) may have different mechanisms in stimulating osteoblast mineralization. In addition, the mRNA expression ratio of osteoprotegerin and the receptor activator of nuclear factor-kB ligand was also dramatically increased by treatment with vitamin K1 (62%), menaquinone-4 (247%), and menaquinone-7 (329%), suggesting that vitamin K may suppress the formation of osteoclast by up-regulating the ratio of osteoprotegerin/receptor activator of nuclear factor-kB ligand in osteoblasts. These results provide compelling evidence that vitamin K1, menaquinone-4, and menaquinone-7 all can promote bone health, which might be associated with elevations in the osteoprotegerin/receptor activator of nuclear factor-kB ligand ratio. Graphical abstract: Image 1 Highlights: Vitamin K species significantly increased osteoblast differentiation and mineralization. Vitamin K1 and K2 have different mechanisms in stimulating osteoblast mineralization. Vitamin K may suppress osteoclast formation by up-regulating the ratio of OPG/RANKL in osteoblasts. Vitamin K promote bone regeneration in cultured osteoblastic MC3T3-E1 cells.